2006
DOI: 10.1093/treephys/26.10.1325
|View full text |Cite
|
Sign up to set email alerts
|

Impact of eastern dwarf mistletoe (Arceuthobium pusillum) infection on the needles of red spruce (Picea rubens) and white spruce (Picea glauca): oxygen exchange, morphology and composition

Abstract: Eastern dwarf mistletoe (Arceuthobium pusillum Peck) is a hemiparasitic angiosperm that infects white spruce (Picea glauca (Moench) Voss) and red spruce (P. rubens Sarg.) in northeastern North America. The effects of mistletoe infection differ substantially between white and red spruce, with white spruce suffering greater infection-induced mortality. In the present study, we sought to determine the role that species-specific differences in needle-scale responses to parasitism may play in the observed differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 31 publications
0
31
1
Order By: Relevance
“…On the other hand, according to Ehleringer et al (1985), Marshall and Ehleringer (1990), Escher et al (2004) xylem parasites and in particular mistletoe species are highly dependent on the supply of organic carbon and nitrogen from their hosts, shrinking the leaf area. Reduction in needle size could be a response to mistletoe infection, because smaller needles would require lower amounts of nitrogen and fixed carbon (Reblin et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, according to Ehleringer et al (1985), Marshall and Ehleringer (1990), Escher et al (2004) xylem parasites and in particular mistletoe species are highly dependent on the supply of organic carbon and nitrogen from their hosts, shrinking the leaf area. Reduction in needle size could be a response to mistletoe infection, because smaller needles would require lower amounts of nitrogen and fixed carbon (Reblin et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the results of Rigling et al (2010) for pine mistletoe (Viscum album ssp. austriacum) and Reblin et al (2006) for dwarf mistletoe (Arceuthobium pusillum).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5C), alter host phytohormone balance, resulting in the formation of dense masses of branches called witches'-brooms (126,159,187). Branches from witches'-brooms exhibit features atypical of uninfected host tissue such as: increased longevity (222); elimination or reduction of seed and cone production (24,116); increased branch elongation on some hosts (83,209); increased biomass compared with uninfected branches of the same age (209); and decreased number, length, and mass of needles (28,29,175). While witches'-brooms are the most easily observed symptom of dwarf mistletoe infection and serve as large nutrient sinks that contribute to the decline of host vigor and growth (136), they also appear to have positive effects in an ecological context (see below).…”
Section: Mistletoes As Pathogensmentioning
confidence: 99%
“…In contrast, Shen, Prider et al (2010) found that Chl a/b ratio of C. scoparius stems increased in response to infection with C. pubescens under ambient light. Most other studies have reported no effect of parasitism on host Chl a/b ratio (Cechin and Press 1994;Hibberd, Quick et al 1996;Jeschke, Baig et al 1997;Logan, Huhn et al 2002;Reblin, Logan et al 2006;Cameron, Geniez et al 2008;Shen, Hong et al 2011;Shen, Xu et al 2013). In our study, both Chl a and Chl b declined to a similar degree in the infected plants in HL, whereas in LL, there was a strong decrease in …”
Section: Impacts Of Infection and Light On L Myrsinoides Pigment Commentioning
confidence: 97%